Ficha Resumen: Triple Restricción y Triple Restricción Ampliada - Víquez-Paniagua, Ana Gabriela (My University, 2017)
El objeto comprende la definición y las variables que conforman la triple restricción y la triple restricción ampliada

The object contains the definition and the parts of the triple restriction and the extended triple restriction.
Keywords: Restricciones; Tiempo; Costos; Riesgos; Satisfacción -- Clientes; Restrictions; Weather; Costs; Risks; Satisfaction - Customers